Communication Patterns in the Use of Communication Features in Online Games Case Study: Valorant - Krisvianty, Gabriela Glory Excelin; Dinansyah, Fakhriy; Bangun, Cendera Rizky Anugrah (UI Scholars Hub, 2024)
Video games are a form of innovation in developing variations in human interaction. They were initially used as a means of entertainment that required direct communication and interaction, now mediated by computers in various forms. In addition, video games consisting of console, mobile, and PC categories have also become competitive sports achievements, thus making gaming activities more competitive and have different communication patterns. The aim of this research is to find out how the communication patterns of online game players use communication features to help win the game. Valorant is an online game that provides communication features in it. This research uses computer-mediated communication theory, virtual communication and gaming as social activity. Case study used in this with observation and interview as techniques to collect data. This study found out that the patterns of communication in the Valorant online games include secondary communication pattern, which means communications run with mediums; singular communication patterns, which is communication where the communicator deliver pieces of information to the communicant as a terminal point; and circular communication patterns which is a communication process where the pieces of information are exchanged in between communicator and communicant and there is function exchange as well.